Non-alcoholic fatty liver disease is associated with a worse prognosis in patients with heart failure: A pool analysis - Qiu, Min; Li, Jiahuan; Hao, Shali; Zheng, Haoxiao; Zhang, Xiaojie; Zhu, Hailan; Zhu, Xiaolin; Hu, Yunzhao; Cai, Xiaoyan; Huang, Yuli (Frontiers in Endocrinology, 2023)
Background and aims Non-alcoholic fatty liver disease (NAFLD) is associated with a higher risk of heart failure (HF) than those without NAFLD. However, the prognostic impact of NAFLD in HF is still controversial. This meta-analysis aimed to explore the association between NAFLD and the risk of adverse outcomes in patients with HF. Methods We searched multiple electronic databases (Embase, PubMed, and Google Scholar) for potentially related studies up to June 30, 2022. Cohort studies reported multivariable adjusted relative risks and 95% confidence intervals (CIs) of adverse outcomes in HF patients with NAFLD comparing those without NAFLD were included for analysis. Results A total of six studies involving 12,374 patients with HF were included for analysis, with a median follow-up duration of 2.5 years. The pooled analysis showed that HF patients with NAFLD were associated with a significantly increased risk of major composite adverse outcomes (HR 1.61, 95% CI 1.25-2.07), all-cause mortality (HR 1.66, 95% CI 1.39-1.98), and HF hospitalization or re-hospitalization (HR 1.71, 95% CI 1.03-2.86). Conclusion NAFLD is associated with a worse prognosis in patients with HF. Effective screening and treatment strategies are needed to improve the prognosis in HF patients with NAFLD.